AI in Academia: Perspectives from the University of Batna 2 on Transforming Education - behloul, abdellah (Journal of Social Sciences and Humanities, 2025)
This article examines the integration of Artificial Intelligence (AI) into higher education at the University of Batna 2, focusing on the perspectives of teachers and students regarding its opportunities and challenges. Utilizing a mixed-methods approach, the study gathers quantitative and qualitative data through surveys and interviews. Findings reveal a general enthusiasm for AI’s potential to personalize learning experiences while highlighting concerns related to data privacy and the diminishing role of human interaction in education. The article concludes with recommendations for effective AI implementation in educational settings, emphasizing the importance of ethical considerations and maintaining personal connections in the learning process.